2020
DOI: 10.3389/fpsyg.2020.01012
|View full text |Cite
|
Sign up to set email alerts
|

Putting a Finger on Numerical Development – Reviewing the Contributions of Kindergarten Finger Gnosis and Fine Motor Skills to Numerical Abilities

Abstract: The well-documented association between fingers and numbers is not only based on the observation that most children use their fingers for counting and initial calculation, but also on extensive behavioral and neuro-functional evidence. In this article, we critically review developmental studies evaluating the association between finger sensorimotor skills (i.e., finger gnosis and fine motor skills) and numerical abilities. In sum, reviewed studies were found to provide evidential value and indicated that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 102 publications
(186 reference statements)
1
25
0
1
Order By: Relevance
“…Along these lines, Bermejo and Lago (1988) clarify and empirically show that the use of materials is very positive at the beginning of the mathematical content learning, although it can be an obstacle once this phase has been overcome. Likewise, some authors defend the importance of the use of fingers in mathematical development ( Barrocas et al, 2020 ; Fischer et al, 2020 ). Therefore, it is convenient to “de-algorithmize” the mathematics classes since the algorithm is only an instrument for solving tasks, and not their ground foundation.…”
Section: General Considerationsmentioning
confidence: 99%
“…Along these lines, Bermejo and Lago (1988) clarify and empirically show that the use of materials is very positive at the beginning of the mathematical content learning, although it can be an obstacle once this phase has been overcome. Likewise, some authors defend the importance of the use of fingers in mathematical development ( Barrocas et al, 2020 ; Fischer et al, 2020 ). Therefore, it is convenient to “de-algorithmize” the mathematics classes since the algorithm is only an instrument for solving tasks, and not their ground foundation.…”
Section: General Considerationsmentioning
confidence: 99%
“…They found that nonsymbolic skills were related to fine motor skills concurrently, while math achievement was predicted indirectly through basic numerical skills. Finally, Barrocas et al (2020) conducted a literature review of contributions of kindergarten fine motor skills to later numerical cognition, finding a "clear contribution of fine motor skills to numerical and mathematical abilities" (p. 9), with fine motor skills predicting counting, number system knowledge, number magnitude processing, and calculation ability.…”
Section: Embodied Cognitionmentioning
confidence: 99%
“…Numerical performance can depend on embodied factors which make mathematics not as abstract as many believe ( Lakoff and Núñez, 2000 ). The body, in particular, the fingers, and the use thereof play a crucial role in numerical development ( Barrocas et al, 2020 ). Here, we focus on different aspects of finger-use in numerical settings, ranging from the use of individual fingers or hands to finger-gnosis , and fine motor skills ( FMSs ).…”
Section: The Showcase Of Finger-use and Numerical Performancementioning
confidence: 99%
“…FMSs capture how well one can move the fingers and are measured by motor-skill tests (e.g., Gashaj et al, 2019 ). A recent review summarizes the role of finger-use for preschool children’s performance in numerical tasks ( Barrocas et al, 2020 ). The authors conclude that finger-use strongly contributes to counting, knowledge of the number system, number-magnitude processing, and calculation ability in childhood.…”
Section: The Showcase Of Finger-use and Numerical Performancementioning
confidence: 99%
See 1 more Smart Citation